2020
DOI: 10.1038/s41598-020-60344-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct surfaces on Cdc5/PLK Polo-box domain orchestrate combinatorial substrate recognition during cell division

Abstract: Polo-like kinases (Plks) are key cell cycle regulators. They contain a kinase domain followed by a polobox domain that recognizes phosphorylated substrates and enhances their phosphorylation. The regulatory subunit of the Dbf4-dependent kinase complex interacts with the polo-box domain of Cdc5 (the sole plk in Saccharomyces cerevisiae) in a phosphorylation-independent manner. We have solved the crystal structures of the polo-box domain of Cdc5 on its own and in the presence of peptides derived from Dbf4 and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…We found that Exo1 interacts with Cdc5 through the same mode as the only example described so far, Dbf4. Besides the importance for the meiotic recombination context, our study therefore adds another case where the recently described interaction surface on Cdc5, distinct from the phosphopeptide recognition surface, promotes interaction with a protein relevant for a biological process (48). This surface is conserved in human PLK, and our work should open new avenues to search for other partners of Cdc5 or human PLKs with similar interacting motifs, and to inhibitors that may specifically target this new interacting surface.…”
Section: Another Example Of Non-canonical Cdc5 Binding To Its Substrates Involving the Rsiega Motifmentioning
confidence: 69%
See 4 more Smart Citations
“…We found that Exo1 interacts with Cdc5 through the same mode as the only example described so far, Dbf4. Besides the importance for the meiotic recombination context, our study therefore adds another case where the recently described interaction surface on Cdc5, distinct from the phosphopeptide recognition surface, promotes interaction with a protein relevant for a biological process (48). This surface is conserved in human PLK, and our work should open new avenues to search for other partners of Cdc5 or human PLKs with similar interacting motifs, and to inhibitors that may specifically target this new interacting surface.…”
Section: Another Example Of Non-canonical Cdc5 Binding To Its Substrates Involving the Rsiega Motifmentioning
confidence: 69%
“…Importantly, mutation of the key residue of this surface (S630Q mutation) abolished interaction with Exo1, as it did for Dbf4, but kept intact the interaction with Spc72, a canonical interacting substrate of Cdc5 (Figs. 5D and S7D) (48). Conversely, mutation of the WHK motif of Cdc5 involved in phosphopeptide recognition (44) did not alter interaction with Exo1 or Dbf4, but reduced interaction with Spc72 (Figs.…”
Section: Cdc5 Directly Interacts With Exo1 To Promote Crossover Formationmentioning
confidence: 85%
See 3 more Smart Citations